EFFECT OF DYNAMICAL WATER QUALITY ON SHRIMP CULTURE IN THE INTEGRATED MULTITROPIC AQUACULTURE (IMTA) - Brata Pantjara; Muhammad Nur Syafaat; Anang Hari Kristanto (Indonesian Aquaculture Journal, 2015)
One of the technologies to improve the productivity of shrimp farms are environmentally friendly shrimp farming multitrophic integrated system known as Integrated Multitrophic Aquaculture (IMTA). The aims of the study were to observe the water quality dynamic on the integrated multitrophic aquaculture and the effect on the production. This study was used four plots which each of pond had 4,000 m2 in sizing, located in experiment pond, at Research and Development Institute for Coastal Aquaculture, Maros. The main commodities used were tiger and vannamei shrimp. In the A pond was cultivated the tiger shrimp with density 12 ind./m2, in B pond was tiger shrimp with density 8 ind./m2, C pond was vannamei shrimp with density 50 ind./m2, and D pond was vannamei shrimp with density 25 ind./m2. Other commodities were red tilapia (Oreochromis niloticus). Each pond had stocking density 2,400 ind./plot which was divided into 5 hapas having a size of (6 m x 4 m x 1.2 m)/each, mangrove oysters (Crassostrea iredalei and Saccostrea cucullata) with density 7,500 ind./4,000 m2 and seaweed (Gracilaria verrucosa) of 500 kg/4,000 m2. The observation of dynamic water quality in the pond was conducted every day i.e. temperature, dissolved oxygen, salinity, and measured pH, while the total organic matter total (TOM), total ammonia nitrogen (TAN), nitrite, nitrate, phosphate were taken every two weeks. The measurements methods of water quality in laboratory was refered to APHA (2008); and Boyd (1990). During the study, absorption of N and P in seaweed were measured, the obtained plankton was identified and the ratio of carbon and nitrogen during the observation was also calculated. To determine the effect of dominant water quality on production was used the principal component analysis (PCA). The result showed that water quality during the study was suitable for shrimp and red tilapia culture. The dominant water qualities which effected the shrimp production in IMTA system were total ammonia nitrogen (TAN), oxygen, total organic matter (TOM), phosphate, and salinity. The survival rate of the tiger shrimp in intensive pond and semi intensive pond was 50.68% and 59.28% respectively, while the survival rate of the vannamei shrimp in intensive and semi intensive was 71.26% and 68.06% respectively. The highest shrimp production in the cultivation of IMTA reached was 1,488 kg/pond (3,720 kg/ha) in C pond. The lowest feed conversion ratio (FCR) was obtained in the D pond (0.89). The highest production of red tilapia in IMTA reached in C pond (426.65 kg/pond).